Performance Information in Local Government Strategy: An Institutional Isomorphism Approach - Wuandari, Futri Ayu; Pageno, Arie Mahardika; Rivai, Dian Rahmayanti (MANDAR: Management Development and Applied Research Journal, 2025)
This study aims to analyze how local government institutions utilize performance information for strategic decision-making, specifically in implementation and evaluation phases, through the lens of institutional isomorphism. The research employs a qualitative method with a case study approach in the Special Region of Yogyakarta, Indonesia. Primary data were collected through in-depth interviews with eight officials selected using purposive sampling. Thematic analysis was conducted following Braun & Clarke’s model. Findings reveal that performance information is often used symbolically due to external pressures rather than for substantive strategic improvement. Coercive isomorphism, driven by regulatory compliance, is the most dominant factor, followed by mimetic and normative pressures. This study theoretically reinforces the relevance of institutional isomorphism and practically highlights the importance of strengthening internal capacity for strategic and sustainable performance management. Novelty of this study contextualizes institutional isomorphism within Indonesia's decentralized local governance and presents qualitative evidence on the distinction between symbolic and substantive use of performance information